Successful Laparoscopic and Endoscopic Cooperative Surgery for a Duodenal Neuroendocrine Tumor: A Case Report - Yamamoto, Manabu; Yano, Hiroko; Kosai-Fujimoto, Yukiko; Kubokura, Naoya; Kobayashi, Hiroyuki; Ohya, Masafumi; Tuneyoshi, Masazumi; Ito, Tetsuhide (Archives of Clinical and Medical Case Reports, 2020)
Neuroendocrine tumors (NET) that develop at the second portion of the duodenum are rare, although most of NET at the duodenum is the first portion. We resected a duodenal NET by using a laparoscopic and endoscopic cooperative surgery (LECS) technique. A 33-year-old man underwent esophagogastroduodenoscopy that revealed a 6 mm, gently raising tumor on the opposite side of the ampulla of vater at the second portion of the duodenum. We performed a full-thickness local excision using the LECS technique. The tumor was confirmed and endoscopically marked along the resection line. After a full-thickness excision, using endoscopic and laparoscopy, closure using a liner stapler was performed laparoscopically. We demonstrated that LECS is a safe and feasible procedure for duodenal G1 NET at the second portion of the duodenum.